Pendampingan Penguatan Tata Kelola Kelembagaan Kelompok Wanita Tani Desa Daon Kecamatan Rajeg Kabupaten Tangerang - Nur Muhamad Iqbal (Universitas Prof. Dr. Moestopo (Beragama), 2026)
The Women Farmers Group (KWT) in Daon Village, Rajeg Subdistrict, has great potential in fostering the village economy but is hindered by weak institutional governance and a non-functional organizational structure. This Community Service (PkM) activity aims to provide structured mentoring in strengthening institutional governance and educating administrators on transparent, accountable, and participatory management principles. The implementation method used the Participatory Action Research (PAR) approach, involving 15 KWT administrators and members through interactive workshops and Focus Group Discussions (FGD). The results showed an increase in participants' understanding of the urgency of business group institutions and good governance principles. Through the FGD session, KWT Desa Daon successfully formulated a comprehensive organizational structure, including clear job descriptions from the chairperson level to operational sections such as production and marketing. This governance strengthening directly implies an increase in member capacity, transparent financial management, and the readiness of KWT to transform into a bankable rural micro-enterprise. In conclusion, this mentoring successfully laid an organized institutional foundation to drive KWT independence and improve the economic resilience of Daon Village.